Islamic Primary Schools in the Netherlands. Issue 1 (2nd January 2016) - Dronkers, Jaap
ABSTRACT: During the last 20 years of the 20th century, Islamic primary schools were founded in the Netherlands thanks to its constitutional "freedom of education" (which allows state-funded religious schools), its voucher system (each school receives the same amount of money per pupil), and school choice by parents. This essay gives some background information about the Dutch system of religious schools and the history of Dutch Islamic schools. 1 I address four aspects of Islamic schools: (a) contradictions around the quality of education in Islamic schools; (b) attitudes and values of pupils and parents in Islamic schools, deviating from the broader Dutch society; (c) serious administrative problems around establishing and running Islamic schools, due to the nonexistence of Islamic Dutch elites and teachers; and (d) negative relations between the current Islam religion and educational performance in modern societies.